Health Service Innovation in Lebak District - Sierfi Rahayu (Universitas Sultan Ageng Tirtayasa, 2023)
The revolution in information and communication technology has caused the existence of an organization to depend on their ability to utilize the technology so that they are able to solve various problems accurately and quickly, including government institutions. Currently, data is a resource that must be maximized by every organization, including government agencies, through the use of technology so that it can be reprocessed into useful information. Business intelligence / BI is an approach that can be used by an organization to build a method and system to get fast information based on large data through the use of technology. This study aims to describe the role of BI in supporting accountability in government institutions. The method used in this research is meta-synthesis with a qualitative approach. The results of the study state that BI can support accountability through five dimensions, namely: transparency, accountability, control activities, responsibility and responsiveness. Data governance is the main aspect that supports the creation of these five dimensions. Not only the needs of the external environment, BI is able to provide accurate information about the internal environment of an organization so that it can improve the quality of data governance for the formulation of more comprehensive policies. The implication of this study is that government institutions must continue to adapt to current technological developments so that accountability can be achieved through the positive side of these technological developments.